When the Damage is Done: Effects of Moral Disengagement on Sustainable Consumption (Journal of Organizational Psychology, 2020)
The present research applies moral disengagement theory to explain consumer responses to socioecological attributes of consumption options (e.g., working conditions, climate impact) in the marketplace. We conducted an online experiment demonstrating that participants were likely to engage in self-serving moral reasoning (i.e., moral disengagement) when a presented consumption option with poor socio-ecological performance was perceived as desirable and when a suitable argument (i.e., moral disengagement cue) was available. Furthermore, moral disengagement reduced moral feelings to forgo a consumption option with poor socio-ecological performance and fostered behavioural intentions towards it. These results provide important implications for scholars and public policy alike.
Keywords: Organizational Psychology; moral disengagement; ethical product attributes; consumer social responsibility; sustainable consumption; socioecological attributes